State Management in Building a New Rural Area in Vietnam: A Research in Muong Tra District, Dien Bien Province - Linh, Pham Nguyen My; Long, Pham Thai; Khanh, Tran Le Quoc; Hương, Nguyen Thi Thu; Nang, Do Thi; Sang, Nguyen Quang (Environmental Management and Sustainable Development, 2021)
Vietnam's rural area accounts for 65% of the population, providing over 70% of the labor force for the national economic sectors, of which 51% of the workforce is working in the agricultural sector. This is a sector that creates many jobs for rural areas, contributing 30% of GDP to the national economy. In the current period and the coming years, Vietnam's rural agriculture still plays an important role in the country's socio-economic development. However, Vietnam's rural areas are facing new difficulties and challenges, the growth of agriculture is slow and unsustainable; Farmers' living standards are low and slowly being improved; The disparity in living standards between urban and rural areas, and between regions and regions is tending to expand, especially in mountainous rural areas with unfavorable natural conditions, with many ethnic minorities living together, the gap between the rich and the poor is increasing. That creates conflicts and instability in society, threatening the sustainable development of the country. This article focuses on analyzing the state management situation on new rural construction in Muong Cha district, Dien Bien province, Vietnam, pointing out the achievements, limitations, causes and some recommendations for improvement. State management on the construction of a new countryside in Muong Cha district, Dien Bien province, Vietnam in the context of world economic integration.